A Community-Informed Approach to COVID-19 Vaccine Roll-Out in Under-served Areas in Chicago - DiVirgilio, Laura; Boshara, Arianna; Hunt, Bijou R.; Jacobs, Jacquelyn; Just, Kate; Johnson, Amy K. (Frontiers in Public Health, 2022)
The availability of the COVID-19 vaccine in the US created an urgent need for strategies to achieve widespread vaccine distribution, but approaches to achieving equitable distribution, including reaching communities of color, varied across the country. To add to the knowledge base around targeted vaccine roll-out among underserved communities, the current study presents results from patient vaccination data and staff interviews conducted at Sinai Chicago, a safety-net healthcare system serving under-resourced communities. A total of 11,313 patients received at least one dose of Pfizer or Moderna COVID-19 vaccine between January and October 2021 at a Sinai Chicago facility. The sample was primarily comprised of Hispanic and non-Hispanic Black persons, with a mean age of 47 years, and was split evenly between female and male individuals. Compared to non-Hispanic White persons, Hispanic persons were 1.4 times more likely to have completed the full course of vaccination, while non-Hispanic Black persons were 40% less likely. People ages 18–24 were less likely to be fully vaccinated compared to all other adult age groups. Compared to privately insured persons, publicly insured persons were 40% less likely to have been fully vaccinated. The vaccine roll-out approach focused on educating the community through town halls and targeted messaging to address common myths and misconceptions about the vaccine, as well as developing the necessary infrastructure to administer the vaccine in a variety of community settings. This study illustrates COVID-19 vaccine roll-out in an under-resourced urban area in Chicago and provides insight on future implementation of vaccine intervention in hard to reach communities.